(untitled) (Damascus University Journal of agriculture sciences, 2021)
Salinity is a major abiotic stress reducing the yield of a wide variety of crops all over the world. This study was conducted to investigate oxidative parameters (H2O2 and MDA levels), antioxidant enzyme activities (SOD, APX and CAT) and gene expression of these antioxidant enzymes in two tomato cultivars (Gabali and Mosyaf) under salt stress treatments (0, 50, 100 and 150 mM NaCl). Salt stress increased H2O2 and MDA contents, as well as the activities of SOD, APX and CAT. The expression of iron SOD (FeSOD) and manganese SOD (MnSOD) genes was upregulated by some concentrations of NaCl in Gabali cultivar, while it was decreased in Mosyaf cultivar at all NaCl concentrations. The expression of cytosolic APX (APXcyt) and thylakoid-bound APX (APXt) genes was increased by the most of NaCl concentrations in the two investigated cultivars. The expression of CAT1 and CAT2 genes was decreased at all NaCl treatments in both the studied cultivars. Our findings suggest that antioxidant enzymes and their gene expressions may be differentially or cooperatively involved in the defense mechanisms of tomato plants exposed to salt stress.